Born to be Wilde - James, Eloisa (New York, NY Avon Books, an imprint of HarperCollinsPublishers, 2018)
Desperate Lavinia Gray gets some unexpected help from Parth Sterling, the richest bachelor in England, with finding a husband, and as they work closely together, she vows to convince him that he is the only man for her.
Keywords: Aristocracy (Social class) -- Fiction; Man-woman relationships -- Fiction; Upper class -- England; Fiction; England -- Fiction; England -- Social life and customs -- 18th century; Fiction; Romance fiction